2018
DOI: 10.37236/7581
|View full text |Cite
|
Sign up to set email alerts
|

Analogies between the Crossing Number and the Tangle Crossing Number

Abstract: Tanglegrams are special graphs that consist of a pair of rooted binary trees with the same number of leaves, and a perfect matching between the two leaf-sets. These objects are of use in phylogenetics and are represented with straightline drawings where the leaves of the two plane binary trees are on two parallel lines and only the matching edges can cross. The tangle crossing number of a tanglegram is the minimum crossing number over all such drawings and is related to biologically relevant quantities, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Before we answer (1), we start with a definition. While a special case of this definition is sufficient for answering (1), the extra generality will be useful later in Section 5.…”
Section: Preserving Subtanglegram Planarity and Reducing Crossingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before we answer (1), we start with a definition. While a special case of this definition is sufficient for answering (1), the extra generality will be useful later in Section 5.…”
Section: Preserving Subtanglegram Planarity and Reducing Crossingsmentioning
confidence: 99%
“…Prior to this, Lozano et al constructed their Untangle Algorithm for drawing a planar layout of a planar tanglegram [15]. Anderson et al recently proved that removing a between-tree edge (t i , s φ(i) ) from a tanglegram reduces the crossing number by at most n − 3, and they produced a family of tanglegrams to show that this bound is sharp [1]. They also found that the maximum crossing number over all tanglegrams asymptotically approaches 1 2 n 2 , where n is the number of leaves in each tree.…”
Section: Introductionmentioning
confidence: 99%
“…constructed their Untangle Algorithm for drawing a planar layout of a planar tanglegram [15]. Anderson et al recently proved that removing a between-tree edge (t i , s φ(i) ) from a tanglegram reduces crossing number by at most n − 3, and they produced a family of tanglegrams to show that this bound is sharp [1]. They also found that the maximum crossing number over all tanglegrams asymptotically approaches 1 2 n 2 , where n is the number of leaves in each tree.…”
Section: Introductionmentioning
confidence: 99%